Diagnostic value of some morphological characteristics useful for discriminating the subgenera ofBombus Latreille s.l. and Psithyrus Lepeletier s.l. (Hymenoptera Apidae Bombinae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The morphology of some structures of legs and last urites, useful fordiscriminating the subgenera of the genera Bombus and Psithyrus is examined.This work completes previous researches of the same Authors,where other characteristics of morphology, particularly females' head andmales' genitalia, were analyzed, in order to draw up a dichotomic keythat summarizes the parameters considered till now.
Keywords: Bombus; Psithyrus; morphology